Influence of passenger car air conditioner system thermostat level setting to fuel consumption and thermal comfort - Kamaruddin, Muhamad Khiril (2015)
Malaysia is a tropical country with very high temperature during the day. Car users in Malaysia need in car air-conditioning system because the weather is hot and humid all year. Passenger adjusts the thermostat level (temperature knob setting) position to regulate the cold air temperature supplied to the cabin. By adjusting the thermostat, it affects the vehicle fuel consumption. When thermostat level is set to the lowest setting, compressor need to be driven on a regular basis and this require power from the engine. With the use of engine power, fuel consumption will increase. Fuel prices are very unstable and can get very high thus the need to lower its consumption. The objective of this study is to measure fuel consumption of different thermostat level setting of the air conditioning system, in the case of stationary cars and without passengers and driver in it. The data in this study were taken in four different modes and the two levels of the selected fan speed. At the same time the cabin temperature is monitored by specific device, to record the temperature, relative humidity and CO2. Fuel consumption was tested by filling 5 liters of petrol into the external tank. After one hour of testing, the total of fuel consumption can be calculated by measuring the amount of fuel remaining. At the end of the experiment, the most practical and suitable thermostat level setting will be propose based on the fuel consumption usage and according to the specifications of the appropriate level of comfort based on parameters such as temperature, relative humidity and CO2. Besides saving on fuel, it is also in this mode that the condition of temperature and humidity in the car’s cabin were found to be most comfortable. Recorded temperature is 25.83ºC, relative humidity 51.72% and CO2 is 553 ppm. The selected mode is at mode 4 low blower fan speed. The fuel consumption in this mode is amounted 1220 litres.